Well-being Index of Elementary School Parents and Students' Perspectives in Batu Pahat, Johor. - Isa, Khairunesa; Sarala Thulasi Palpanadan,; Hazilah Kadir@Shahar,; Mansor Abu Talib,; Siti Nur Asiyah,; Siti Khorriyatul Khotimah,; Abdul Muhid4,; Moch. Irfan Hadi, (Human Sustainability Procedia, 2024)
Students’ lives can be quite stressful as a lot of pressure and stress may affect their well-being at school. The purpose of this study was to create and test the tools that could measure elementary school well-being based on four components: environment, social, achievement, and health, which were recreated by following both cognitive and affective aspects. Two schools in the district of Batu Pahat, Johor, were chosen as sampling sites by providing the printed questionnaire to be answered by students in grades five and six as well as their parents. In this study, reliability analysis, descriptive information, and mean analysis were tested to measure the reliability and the elementary school well-being index. The mean data were drafted to observe the precision between students and parents. The results showed that parents' perceptions of their children's well-being were precise but slightly higher than what their children felt at school. Besides, the results showed that the students did well in the social element with a mean value of 4.450, followed by health, environment, and achievement with a mean score of 4.152, 4.006, and 3.900, respectively. The outcomes of the study might help educational institutions, government officials, and policymakers to teach good values and raise awareness about student attitudes toward their studies.